PENGGUNAAN PREDIKAT DALAM HARIAN RIAU POS - Devi Winda Rini Simanungkalit; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to describe and categorize the form of predicate and the type of predicate word class contained in the news text of the main page of the Riau Pos Daily. This type of research is qualitative research with a descriptive analysis research method that aims to clearly explain the data described about the form of predicates and the types of predicate word classes contained in the Riau Pos Daily. The source of this research data is the news text about the Covid-19 Pandemic on the main page of the Riau Pos Daily. This research was conducted in Pekanbaru, Riau. The data in this study is a predicate in a sentence in a news text. The data are analyzed, then classified according to the form and category of the word class. Based on the results of the study, 3 predicate forms and 4 categories of word classes were found with a total of 117 data. The first division of the data is (1) word-shaped predicates totaling 73 data, (2) phrase-shaped predicates totaling 36 data, and (3) clause-shaped predicates totaling 8 data. The division of the two data is (1) verb category predicates totaling 72 data, (2) predicates categorized as nomina as many as 10 data, (3) adverbial category predicates as many as 27 data, (4) numeralia category predicates as many as 6 data, and there are 2 particle-shaped data.Keywords : predicate, word class, predicate form, category